The development of parents-infant relationship in high-risk pregnancies and preterm birth - Camilla Pisoni; Francesca Garofoli; Ilaria Baiardini; Chryssoula Tzialla; Mauro Stronati (Hygeia Press di Corridori Marinella, 2014)
The theory of human attachment, developed in 1951 by John Bowlby, has been widely applied across psychological, medical and social disciplines, especially in the context of developmental psychology; more recently it has been studied in the obstetric and neonatal fields. Numerous studies suggest that attachment patterns have an impact on the social, cognitive and emotional development of the off-spring, and are also believed to influence the individual's psychosocial trajectories across the lifespan. Starting from empirical study of attachment, the psychological analysis of the experience of pregnancy allowed to introduce the concept of prenatal attachment, considered as the earlier internalized representation of the fetus that both parents acquire and elaborate during pregnancy. Recent studies have attempted to investigate how prenatal attachment develops in conditions of hazard, as for example in women hospitalized for a high-risk pregnancy or preterm birth. Literature showed that these clinical conditions may represent risk factors that, along with psychological distress and lack of familiar and social support, may adversely affect the mother-child relationship, with consequences on the psycosocial development of the off-spring. During pregnancy, medical team should assess mothers' distress and attachment, perform procedures to positively develop attachment, and direct parents with low attachment scores to receive a professional, specific counseling. In the premature birth context, it is important to closely support mother-infant contact and to decrease maternal stress in every possible way during hospitalization and after discharge. Promotion of psychological wellbeing and attachment during pregnancy and after birth may serve as a crucial opportunity of improving maternal health practices, perinatal health and neonatal outcomes.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou